Reviews (New blackfriars, 1968)
THE COMMUNITY WITNESS: AN EXPLORATION OF SOME OF THE INFLUENCES AT WORK IN THE NEW TESTAMENT COMMUNITY AND ITS WRITINGS, by Hamish F. G. Swanston WATER AND THE SPIRIT, a study in the relation of baptism and confirmation, by Cyril E. Pocknee LITURGY IS WHAT WE MAKE IT, by Oliver and lanthe Pratt. THE LIVING GOD AND THE MODERN WORLD, by Peter Hamilton SCIENCE AND FAITH IN TEILHARD DE CHARDIN (Teilhard Study Library, Vol. 1), by Claude Cué EVOLUTION, MARXISM AND CHRISTIANITY QUIS CUSTODIET? The Newman Association A QUESTION OF CONSCIENCE, by Charles Davis